2010
DOI: 10.1016/j.fishres.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of mackerel (Scomber scombrus L.) after pursing and slipping from a purse seine

Abstract: Havforskningsinstituttets institusjonelle arkiv Brage IMR - Institutional repository of the Institute of Marine Research b r a g e i m rDette er forfatters siste versjon av den fagfellevurderte artikkelen, vanligvis omtalt som postprint. I Brage IMR er denne artikkelen ikke publisert med forlagets layout fordi forlaget ikke tillater dette. Du finner lenke til forlagets versjon i Brage-posten. Det anbefales at referanser til artikkelen hentes fra forlagets side. Ved lenking til artikkelen skal det lenkes til po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…In contrast, in certain purse seine fisheries, in which slippage takes place, mortality of slipping fish may constitute an important fraction of the catch; Stratoudakis and Marcalo (2002) estimated that slipping fish make up 69% of the catch in Portuguese purse seines targeting sardine. Mortality of slipping fish (or non-catch mortality) is considered to be a source of error for stock assessment and fisheries management (Mitchell et al 2002, Stratoudakis and Marcalo 2002, Huse and Vold 2010 and it is a knowledge gap for all gears. Most of this mortality, which mainly occurs due to injuries of the escaping fish, may be species-specific, density-dependent ( Huse andVold 2010, Marcalo et al 2010) and may even vary across space and time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in certain purse seine fisheries, in which slippage takes place, mortality of slipping fish may constitute an important fraction of the catch; Stratoudakis and Marcalo (2002) estimated that slipping fish make up 69% of the catch in Portuguese purse seines targeting sardine. Mortality of slipping fish (or non-catch mortality) is considered to be a source of error for stock assessment and fisheries management (Mitchell et al 2002, Stratoudakis and Marcalo 2002, Huse and Vold 2010 and it is a knowledge gap for all gears. Most of this mortality, which mainly occurs due to injuries of the escaping fish, may be species-specific, density-dependent ( Huse andVold 2010, Marcalo et al 2010) and may even vary across space and time.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality of slipping fish (or non-catch mortality) is considered to be a source of error for stock assessment and fisheries management (Mitchell et al 2002, Stratoudakis and Marcalo 2002, Huse and Vold 2010 and it is a knowledge gap for all gears. Most of this mortality, which mainly occurs due to injuries of the escaping fish, may be species-specific, density-dependent ( Huse andVold 2010, Marcalo et al 2010) and may even vary across space and time. Hence, for selective gears with low discard ratios, like purse seines, more effort should be placed on estimating the mortality rate at sea instead of analysing the discard mortality further, especially when the budget is limited.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing fishing techniques, handling practices, and environmental variables with postrelease outcomes (Davis 2002), research can inform management efforts to reduce or account for postrelease mortality (e.g., Huse and Vold 2010;Gale et al 2011;Roberts et al 2011;Baker et al unpublished data) or improve animal welfare (e.g., Butcher et al 2011). Fisheries capture involves two general biological effects at the organism level: physiological stress and injury.…”
Section: Spawning Salmon Resilience To Capture 525mentioning
confidence: 99%
“…In terms of mitigation, they suggested that information should be collected from fishers and fisher organizations, and creeping should then be carried out at locations where fishers have reported incidences of lost or abandoned nets. Huse & Vold (2010) showed that (short-term) mortality of mackerel in purse seines could be reduced by avoidance of 'excessive crowding' of the fish. Studies by Stratoudakis & Marcalo (2002) on sardine (Sardine pilchardus) taken by purse seiners in Portugal and for another sardine species (Sardinops sagax) taken with the same gear in western Australia (Mitchell et al, 2002) indicate that slippage mortality could be much higher in the long-term as, although fish are still alive when released, many are believed to have suffered physical damage (loss of scales, skin abrasions) by contact with other fish and the walls of the net.…”
Section: On the Impact Of Fishing And Discards In The Ecosystemmentioning
confidence: 99%
“…This is also destructive because the fish are often killed during the capture process (e.g. FAO, 2010;Huse & Vold, 2010).…”
Section: Introductionmentioning
confidence: 99%